A Simple Flow Classification Parameter Can Discriminate Rupture Status in Intracranial Aneurysms. Issue 5 (November 2020) - Asgharzadeh, Hafez; Shahmohammadi, Ali; Varble, Nicole; Levy, Elad I; Meng, Hui; Borazjani, Iman
Abstract : BACKGROUND: : A simple dimensionless aneurysm number ( An ), which depends on geometry and flow pulsatility, was previously shown to distinguish the flow mode in intracranial aneurysms (IA): vortex mode with a dynamic vortex formation/evolution if Symbol, and cavity mode with a steady shear layer if Symbol . OBJECTIVE: : To hypothesize that Symbol can distinguish rupture status because vortex mode is associated with high oscillatory shear index, which, in turn, is statistically associated with rupture. METHODS: : The above hypothesis is tested on a retrospective, consecutively collected database of 204 patient‐specific IAs. The first 119 cases are assigned to training and the remainder to testing dataset. An is calculated based on the pulsatility index ( PI ) approximated either from the literature or solving an optimization problem (denoted asSymbol ). Student's t ‐test and logistic regression (LR) are used for hypothesis testing and data fitting, respectively. RESULTS: : An can significantly discriminate ruptured and unruptured status with 95% confidence level ( P < .0001). An (using PI ) and Symbol (using Symbol ) significantly predict the ruptured IAs (for training dataset Symbol AUC = 0.85, Symbol AUC = 0.90, and for testing dataset Symbol sensitivity = 94%, specificity = 33%, Symbol sensitivity = 93.1%, specificity = 52.85%). CONCLUSION: : Symbol predicts ruptured status. Unlike traditional hemodynamic parameters such as wall shear stress and oscillatory shear index, An has a physical threshold of one (does not depend on statistical analysis) and does not require time‐consuming flow simulations. Therefore, An is a simple, practical discriminator of IA rupture status.